2022
DOI: 10.1371/journal.pone.0264511
|View full text |Cite
|
Sign up to set email alerts
|

Relationship satisfaction in the early stages of the COVID-19 pandemic: A cross-national examination of situational, dispositional, and relationship factors

Abstract: The outbreak of the COVID-19 pandemic has had a large impact on various aspects of life, but questions about its effects on close relationships remain largely unanswered. In the present study, we examined perceived changes in relationship satisfaction at the beginning of the COVID-19 pandemic by using an international sample of 3,243 individuals from 67 different countries, mostly from Italy, the United States, the United Kingdom, Germany, Austria, and Switzerland. In April and May 2020, participants responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 43 publications
5
27
0
4
Order By: Relevance
“…We found that, on average, individuals reported lower relationship satisfaction, lower appreciation, and lower intimacy during COVID-19, as compared with pre-COVID levels. This is in line with a large cross-national study (data from 68 countries) reporting a general decline in relationship satisfaction using retrospective ratings for pre-pandemic levels ( Vigl et al, 2022 ). In contrast, relationship conflict did not significantly change over time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that, on average, individuals reported lower relationship satisfaction, lower appreciation, and lower intimacy during COVID-19, as compared with pre-COVID levels. This is in line with a large cross-national study (data from 68 countries) reporting a general decline in relationship satisfaction using retrospective ratings for pre-pandemic levels ( Vigl et al, 2022 ). In contrast, relationship conflict did not significantly change over time.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we focused on individuals who cohabit with their partner and our findings might not generalize to non-cohabiting couples. Findings from Vigl et al (2022) emphasize that the pandemic might have differentially impacted partners depending on their living situation, showing that relationship satisfaction showed greater decreases for non-cohabiting, as compared with cohabiting partners, and that joint activities and physical intimacy increased and time for oneself decreased for cohabiting partners, whereas non-cohabiting individuals showed the reverse pattern. Utilizing bivariate latent change score models, we were able to examine coupled associations of study outcomes measured prior to the pandemic with later change in these outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Relationship satisfaction was positively associated with secure attachment and negatively with avoidant attachment for males and females, but ambivalent attachment was linked to low satisfaction only for females [46]. Preoccupied attachment had stronger negative effects on perceived relationship quality for females than other attachment patterns [47]. In other studies, men who are high in avoidance and men and women who are high in anxiety reported lower relationship quality [48], but secure attachment was only positively linked with male satisfaction [45,49].…”
Section: Introductionmentioning
confidence: 73%
“…Besides, a decreasing trend could also be seen in college students’ experience of romantic relationships during the COVID-19 period due to the lockdown policy which reduced the amount of time staying together ( 13 ), with Vigl and colleagues attributing this to limited time staying together under lockdown policy for non-cohabiting couples (college students). Moreover, under such stressful circumstances, positive emotions and expression of feelings might have a beneficial effect on individuals’ attitudes toward their partners, which are highly correlated with their romantic experience and subjective wellbeing ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%